DESCRIPTION OF SMALL INTESTINE HYSTOPATOLOGY OF KAMPUNG CHICKEN GIVEN HERBAL MADICINE ASHITABA AND AVIAN INFLUENZA VACCINE - Arta Guna, I Putu Sandika; Sudira, I Wayan; Setiasih, Ni Luh Eka (Buletin Veteriner Udayana, 2022)
This study aims to determine the effect of giving Ashitaba leaf herbal medicine ( Angelica keiskei ) which was given orally against the histopathological features of the small intestine of native chickens vaccinated with Avian influenza. The sample used in this study were 25 heads day old chicken native chickens, which were divided into 5 treatment groups. The first treatment was (P0) without being given ashitaba leaf herbal medicine but given aquadest, group (P1) was given ashitaba leaf herbal with a concentration of 50mg / head / day, (P2) at a dose of 100mg / head / day, group (P3) with a dose of 200mg / head / day, and (P4) at a dose of 400mg / head / day. The treatment is carried out every day for 14 days from day 8 to day 21 which is given orally by mixing drinking water and ashitaba leaf herbal powder until the volume is 100. ml. On the 21st day, all groups of chickens were vaccinated with the vaccine Avian influenza. On the 42nd day, the experimental native chicken was necropsed, then the small intestine was taken to see changes in the histopathological structure with Hematoxylin-Eosin ( HE) staiuning. The variables examined included hydrophic degeneration, inflammatory cell infiltration and necrosis. The data obtained was tested Kruskal-Wallis. Statistical test results obtained P-value hydrophic degeneration (P = 1,000), inflammatory cell infiltration (P = 0,833) and necrotic lesions (P = 0,983). The results of this study indicate that giving the ashitaba leaf herbal medicine ( A. keiskei ) with a dose range of 50 mg / head / day to a dose of 400 mg / head / day for 14 days had no significant effect on the histopathological picture of the small intestine of native chickens seen from hydrophic degeneration, inflammatory cell infiltration and necrosis.